Comparative analysis of a High Rise Building Frame Considering Two Different Seismic Regions using ETABS - Rajan Nayak; Divya Kotecha; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2022)
Structural developments are increasing rapidly now-a-days throughout the world. Natural calamities like earthquake are happening frequently around the world, hence, the structure has to be designed for the same. The critical seismic analysis of reinforced concrete building, specifically involves the understanding behavior of structure under lateral loads unlike the usual gravity loads such as dead loads and the live loads. Multistorey building would be the greater part influenced by quake constrains to seismic prone areas. The major concern in the design of the multi-storey building is the structure to have enough lateral stability to resist lateral forces, buckling, to control lateral drift and displacement of the building. In order to design an earthquake resistant structure, G+12 story is analyzed for two different seismic zones, one location at Bhuj Gujarat and other location at Jabalpur, Madhya Pradesh and soil types as per IS 1893:2016. Further the behavior of the structure was investigated for the parameters such as Natural period, Displacement, Base shear, Story Stiffness and Story Drift.